Management of Ectopia Lentis in Children - Shehla Rubab, Khair Ahmed Choudhary, Sorath Noorani, Ayesha Khan (Pakistan Journal of Ophthalmology, 2007)
Purpose: To study the etiology, mode of presentation and visual outcome of ectopia lentis after lensectomy in pediatric age group. Materials and methods: This prospective, non comparative, interventional study was conducted in the department of Pediatric Ophthalmology, Al Shifa Trust Eye Hospital, Rawalpindi, Pakistan, from November 2005 to October 2006. Fifty patients, 2.5 to16 years of age, who presented with subluxated lenses both syndromic and non syndromic, were included in the study. Patients with secondary subluxation of lenses were excluded. Patients were selected for surgery having best corrected visual acuity 6/30 or less, pupil block glaucoma, cataract or clear subluxated lenses bisecting the pupil. Surgical technique used was within the bag lensectomy and anterior vitrectomy via limbal approach. Aphakia was treated with glasses or contact lenses followed by amblyopia treatment. Results: Ninety six eyes of 50 patients were included in the study. Twenty six patients (52%) were male and 24 were (48%) female. All had bilateral subluxated lenses. Twelve patients (24%) had familial ectopia lentis, 11(22%) had Marfan’s syndrome, 24 (48%) cases were sporadic, 2 patients (4%) had Weil Marchesani syndrome and 1 (2%) patient had suspected homocystineuria. Within the bag lensectomy was performed on 54 out of 96 eyes (56%) of 34 patients. Twenty nine (54%) out of 54 eyes had BCVA less than 6/30, 7(13%) eyes presented with pupil block glaucoma, 11 (20%) eyes had cataractous subluxated lens, 4 (7.5%) eyes had clear subluxated lenses bisecting the pupil and anterior dislocation in 3 eyes (5.5%) . Other twenty eight eyes (18 pts) out of 96 eyes were given refractive error correction and kept on follow up for progression of subluxation and intraocular pressure monitoring. Preoperatively 32 (59%) out of 54 eyes had visual acuity of hand movements to 6/60 and 22 (41%) eyes had 6/48 to 6/30. Postoperatively BCVA ranged between 6/18 to 6/15 in 29 (54%) eyes, 6/12 to 6/7.5 in 09 (17%) eyes, 6/48 to 6/24 in 5 (9%) eyes. Eleven (20%) eyes achieved 6/60 or less. Forty three (80%) out of 54 eyes showed post operative improvement in BCVA ranging from two to nine lines on ETDRS chart. Conclusion: Within the bag lensectomy via limbal approach is a safe and effective procedure for management of ectopia lentis in pediatric age group. Aphakia corrected by glasses or contact lenses is not ideal but safer than scleral fixation of IOL and implantation of anterior chamber IOL in children.